Exposure to the Family Wellbeing program and associations with empowerment, health, family and cultural wellbeing outcomes for Aboriginal and Torres Strait Islander peoples: a cross-sectional analysis ... - Williamson, Leonie Malezer; Baird, Leslie; Tsey, Komla; Cadet-James, Yvonne; Whiteside, Mary; Hunt, Nadine; Lovett, Raymond (figshare, 2023)
Abstract Background Empowerment is an internationally recognised concept commonly incorporated in First Nations and in this instance Aboriginal and Torres Strait Islander health and wellbeing programs. The Family Wellbeing Program is an empowerment program developed in partnership with Aboriginal and Torres Strait Islander peoples that has been widely delivered to Aboriginal and Torres Strait Islander communities across Australia for close to 30 years. To date, there has been limited quantitative analysis of how this program is linked to health and empowerment outcomes. Methods Cross sectional analysis of Mayi Kuwayu, the National Study of Aboriginal and Torres Strait Islander Wellbeing, baseline data (n = 9,843) recruited using multi-mode random sampling including mail out survey and in community convenience sampling. Logistic regression models were performed to calculate Prevalence Ratios (PRs) and 95% Confidence Intervals (CIs) to examine the association between personal control, life satisfaction, ...